Radiation Safety Issues in Fluoroscopy During Percutaneous Nephrolithotomy - Kumar, Pratik (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: Fluoroscopy-guided intervention during percutaneous nephrolithotomy (PCNL) has become the order of the day. During this procedure, both the patient and the physician are exposed to some radiation. Measurement of radiation doses in patients and personnel are important. Patient radiation doses are used for comparison with other centers for achieving the best possible radiation practice. In addition, there are performance checks for the fluoroscopy machines so that x-ray emitting machines should work at the optimum level ie, producing good images at minimum possible radiation doses. Material and Methods: This is a review of literature and discussion on radiation dose to patients and personnel, and on basic radiation safety tenets and their application in urological interventions of PCNL procedure. Results: Radiation doses during PCNL have gone down over the time due to advances in technology. However, as radiation is hazardous, there is no room for complacency. A hospitalâ€™s medical physicist may ensure even further reduction of x-ray dose by carrying out regular dosimetry and quality assurance tests on the fluoroscopy machines. A survey meter may provide an easy and quicker but not-so-accurate method for occupation exposure determination. Conclusion: The practice of PCNL procedures seems to be quite safe with radiation point of view. The quick, easy, and economical method of estimation of radiation dose using survey meter may need further calibration with the standard thermoluminescence dosimetry method. Setting optimum x-ray parameters, incorporation of filters, and quality assurance tests are a few areas where medical physicists may help in further reduction of radiation doses.